DO SOCIAL MEDIA MARKETING ELEMENTS AFFECT CONSUMER BRAND ENGAGEMENT AND BRAND KNOWLEGDE? CASE STUDY OF NETFLIX INDONESIA - Evita Fitriyani; Erlita Ridanasti (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Social media is one of the most popular tools for brands to market their products and services. The ease and effectiveness of social media features can bring brands closer to consumers and also reach a wider market. This study aims to examine the effect of social media marketing elements on consumer brand engagement so as to increase brand knowledge. This study used 160 samples taken by purposive sampling from users of the Netflix Indonesia’s movie streaming service and Netflix Indonesia’s active followers on Instagram. Data processing in this study used the Structural Equation Modeling (SEM) technique with the SmartPls 3.29 test tool. The results of this study found that entertainment, customization, word of mouth, and trendiness have a positive and significant impact on consumer brand engagement. Meanwhile, interaction has less influence on consumer consumer brand engagement. This research also proves that consumer brand engagement has an influence on brand awareness and brand image. Keywords: SMM, CBE, Brand Knowledge